2020
DOI: 10.1002/chem.202004623
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Simultaneous Doping of Ceria Nanorods with Cu and Cr on CO Oxidation and NO Reduction

Abstract: Ceria particles play a key role in catalytic applications such as automotive three‐way catalytic systems in which toxic CO and NO are oxidized and reduced to safe CO2 and N2, respectively. In this work, we explore the incorporation of Cu and Cr metals as dopants in the crystal structure of ceria nanorods prepared by a single‐step hydrothermal synthesis. XRD, Raman and XPS confirm the incorporation of Cu and Cr in the ceria crystal lattices, offering ceria nanorods with a higher concentration of oxygen vacancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 80 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…Other groups have shown that morphology control is possible: samples with 5 and 10 mol% Cu were made using chlorides and H2O2 heated at 180 °C, and 5 h of heating produced spheres with diameters of 60-80 nm, Figure 4, [57], while addition of PVP, ammonia and urea to the mixture with heating for 6 h gave spheres of ~100 nm in diameter [58]. Rood et al were able to synthesise Cu-containing ceria nanotubes that were single phase up to 7 mol% Cu [59]. Their method involved using Ce(NO3)3 and CuSO4 in NaOH solution heated to 100 °C for 10 h. In the same work, Cr-containing ceria nanotubes, up to a concentration of 5 mol%, were reported where a similar method was used, with Cr(NO3)3 as a precursor.…”
Section: Transition Metal-substituted Ceriasmentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups have shown that morphology control is possible: samples with 5 and 10 mol% Cu were made using chlorides and H2O2 heated at 180 °C, and 5 h of heating produced spheres with diameters of 60-80 nm, Figure 4, [57], while addition of PVP, ammonia and urea to the mixture with heating for 6 h gave spheres of ~100 nm in diameter [58]. Rood et al were able to synthesise Cu-containing ceria nanotubes that were single phase up to 7 mol% Cu [59]. Their method involved using Ce(NO3)3 and CuSO4 in NaOH solution heated to 100 °C for 10 h. In the same work, Cr-containing ceria nanotubes, up to a concentration of 5 mol%, were reported where a similar method was used, with Cr(NO3)3 as a precursor.…”
Section: Transition Metal-substituted Ceriasmentioning
confidence: 99%
“…Their method involved using Ce(NO3)3 and CuSO4 in NaOH solution heated to 100 °C for 10 h. In the same work, Cr-containing ceria nanotubes, up to a concentration of 5 mol%, were reported where a similar method was used, with Cr(NO3)3 as a precursor. These materials were tested as catalysts for both CO oxidation and NO reduction, with the Cu samples outperforming pure CeO2 in terms of CO oxida- Rood et al were able to synthesise Cu-containing ceria nanotubes that were single phase up to 7 mol% Cu [59]. Their method involved using Ce(NO 3 ) 3 and CuSO 4 in NaOH solution heated to 100 • C for 10 h. In the same work, Cr-containing ceria nanotubes, up to a concentration of 5 mol%, were reported where a similar method was used, with Cr(NO 3 ) 3 as a precursor.…”
Section: Transition Metal-substituted Ceriasmentioning
confidence: 99%
“…[32] The Cu 2p spectra (Figure 4c) reveal that the copper dopants embrace Cu 2 + and Cu + species, as evidenced by the observation of the two typical peaks at 934.8 eV and 933.4 eV. [21,25] Interestingly, the low coordinated Cu + species was not detected in the CuCrCe catalysts, due to the coupling of the redox cycles of Cr VI /Cr III and Cu II /Cu I , i. e. the Cu + species can be easily oxidized to Cu 2 + by Cr 6 + species consistent with the results of H 2 -TPR (Figure 2b). [33] It is another indication of the co-existence of the copper and chromium in the CuCrCe catalysts.…”
Section: Chemcatchemmentioning
confidence: 96%
“…[23] In a previous comparative study of different configurations of copper-ceria catalysts, we showed that a solid solution with copper incorporated into the ceria lattice exhibits superior catalytic performance in the NO reduction with CO compared to corresponding catalysts made up of copper oxide particles supported on ceria and ball-milled mechanical mixtures of these components. [24] Recently, Rood et al demonstrated that copper and chromium doping into the crystal lattice of ceria nanorods exposing the (111) facets increases the concentration of oxygen defects and the surface and bulk reducibility leading to enhanced N 2 -selectivity in the reduction of NO with CO. [25] These findings prompted us to prepare multicomponent CuCrCeO x , CuCeO x , and CrCeO x solid solution catalysts to study the synergy of Cu and Cr co-doping in the NO reduction with CO in the presence as well as absence of oxygen and to evaluate the influence of water and SO 2 on the catalyst stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation